Pengaruh Non Performing Loan dan BI Rate terhadap Return on Asset Pada Bank Umum - Jonathan Darmawan; Banter Laksana; Dimas Sumitra Danisworo (Indonesian Journal of Economics and Management, 2020)
The research aims to know the effect of Non Performing Loan (NPL) and Interest Rate of Bank Indonesia towards Return On Asset (ROA). Population in this research are listed commercial bank on Indonesia Stock Exchange (IDX) period in 2014 – 2018. The sampling of the research was performed using the method of purposive sampling. Obtained by amount sample as much 33 bank from 45 commercial banking company listed on Indonesian Stock Exchange in period 2014 – 2018. Research methodology on this research using associative method with quantitative approachment. Data analysis technique used are multi linear regression using IBM SPSS Statistic 24 for Windows software. The result of the survey encountered that partially Non Performing Loan (NPL) had a negative effects toward Return On Asset (ROA) and significant and Interest Rate of Bank Indonesia had a negative effects toward Return On Asset (ROA) and significant. Simultaneously that Non Performing Loan (NPL) and Interest Rate of Bank Indonesia had a significant effect towards Return On Asset (ROA).